Enhancing teacher education for inclusion - (:unkn) unknown (My University, 2020)
As the demographic profiles of many education systems continue to change, the challenges facing the teaching workforce and how teachers are prepared to address different aspects of diversity are leading many European countries to reform teacher education policy in support of inclusive education. This move aligns with the 2018 European Union Council Recommendation on promoting common values, inclusive education, and the European dimension of teaching, which noted that: [h]igh quality inclusive education and training at all levels, is essential in ensuring social mobility and inclusion … and a deeper understanding of our common values (European Commission 2018, p1). As an implementing measure, the Commission recommended that teachers, school leaders and academic staff be enabled to: promote common values and deliver inclusive education, through: (a) measures to empower teachers, school leaders and academic staff helping them convey common values, and promote active citizenship while transmitting a sense of belonging and responding to the diverse needs of learners (17).
PUBLISHED
Keywords: Education; Teachers; Inclusion; Inclusive Society; EDUCATION; Teacher Education; Attitudes; Education